2020
DOI: 10.1002/rra.3686
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and ability of a cyprinid (Schizopygopsis younghusbandi) to cope with accelerating flows when migrating downstream

Abstract: The migration corridors in regulated rivers lead downstream fish migrants, particularly juveniles to pass through water infrastructure. Accelerating flow, experienced by fish, might trigger avoidance behaviour and then influence the downstream migration efficacy. It is essential to understand the causes of avoidance behaviour exhibited by downstream migratory fish in accelerating flow. In this study, the effect of three different accelerating flows on the downstream migration behaviour of Schizopygopsis youngh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…The momentary locomotion also provides clues for the different early performances of downstream migration. To investigate the self‐defence manifestation of downstream fish migrants before the entrance of downstream passages, plenty of studies concentrate on determining the escape behaviour, which is related to the acceleration magnitude of attraction flow in front of the intake, and the critical responses of fish that allow them to switch swimming patterns and prevent entrainment (Li et al, 2020; Vowles & Kemp, 2021). For example, behavioural observation on juvenile Pacific salmonids ( Oncorhynchus gorbuscha ) revealed that flow acceleration, rather than other flume configurations, elicited the avoidance of test fish when the hydraulic conditions changed rapidly (Kemp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The momentary locomotion also provides clues for the different early performances of downstream migration. To investigate the self‐defence manifestation of downstream fish migrants before the entrance of downstream passages, plenty of studies concentrate on determining the escape behaviour, which is related to the acceleration magnitude of attraction flow in front of the intake, and the critical responses of fish that allow them to switch swimming patterns and prevent entrainment (Li et al, 2020; Vowles & Kemp, 2021). For example, behavioural observation on juvenile Pacific salmonids ( Oncorhynchus gorbuscha ) revealed that flow acceleration, rather than other flume configurations, elicited the avoidance of test fish when the hydraulic conditions changed rapidly (Kemp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, 2020;Zhu, Chen, Yang, Ma, & Li, 2017). The S. younghusbandi juveniles (11.17 ± 1.39 cm) in the field experiment proved to be unable to stay in the 0.73-m/s flow region for long periods (M. Li et al, 2020). The sustained swimming speed of S. o'connori (13.4 ± 1.9 cm) in the laboratory has been found to be up to 0.6 m/s.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly the flow velocity for juvenile Schizopygopsis younghusbandi avoiding downstream was near their U crit of 1.11 m/s (Li et al, 2020). Endurance was intended to identify flow velocities that fish could resist long enough to avoid becoming entrained into the turbines.…”
Section: Application Of Swimming Capability Data On Fishway Designmentioning
confidence: 99%